(untitled) (Bioresearch Communications, 2021)
Onion is an inevitable part of our food habits. Fungal infection is one of the major reasons of onion spoilage which not only cause economic losses but also may cause public health threat through mycoses and mycotoxicoses. A total 15 onion samples from different places in Chattagram, Bangladesh were collected to assess the fungal contaminants.Onion consumers along with retailers were interviewed to evaluate their awareness about fungal food spoilage and associated health risk. Three different fungal species were identified and isolated by analysing their macroscopic and microscopic features. These isolates were Aspergillus niger, Aspergillus flavus, and Penicillium spp. A. niger was the most prevalent and found in 14 samples out of 15. Biochemical characterization of the isolated fungi was also done to assess their ability to produce extracellular enzymes and amylase, protease, and cellulase activities were observed. Survey data showed that only around 20% of the interviewees had some idea about fungal contamination, while nearly about 80% of them believed that washing, sunburn and cooking can make the food safe. Bioresearch Commu. 8(1): 1068-1076, 2022 (January)